Schwannoma: A surgical epidemiology - Muhammad Usman Khalid; Mashal Murad Shah; Mohammad Hamza Bajwa; Karim Rizwan Nathani; Altaf Ali Laghari; Muhammad Faraz Raghib; Saad bin Anis; Naveed Zaman Akhunzada; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the surgical incidence and prevalence of schwannoma in our region and quantify the demographic, surgical, neoplastic, and outcome characteristics of the patients diagnosed with schwannoma. Methods: A retrospective cross-sectional study was conducted from January 1 to December 31, 2019. Enrolled were 32 of the highest volume neurosurgical centres in Pakistan. Patients with a histopathological diagnosis of schwannoma and radiological imaging were included in the study. Medical records were reviewed for data, and SPSS version 25 was used for statistical analysis. Patients were followed up for one year, which was the duration of the study. Results: From 2750 patients diagnosed with brain tumours, 148 patients had schwannomas. Out of these, 84 (56.8%) patients were male, and 64 (43.2%) patients were female. The mean age of the patients was 39 ± 14 years. The socioeconomic statuses of the enrolled patients were lower in 72 (53.3%) patients, middle in 57 (42.2%) patients, and upper middle to upper in 6 (4.4%) patients. All patients underwent surgery, 14 patients received radiotherapy, and two patients received chemotherapy. In our cohort, 115 (77.7%) patients presented to public sector hospitals, with only 33 (22.3%) patients presenting to private hospitals. At the end of the study period, 60 (40.5%) patients had been lost to follow-up. Of the remaining 88 patients, 75 (85.2%) were alive. The mortality rate on a one-year follow-up was 14.8%. Conclusion: Schwannoma comprises a larger percentage of the brain tumours in our regions than reported in the literature. The high mortality rate is of particular concern and warrants further investigation to improve patient care and outcomes. Keywords: Schwannoma, Brain neoplasm, Retrospective study, Epidemiology, LMIC Continue...